2015
DOI: 10.1158/1538-7445.am2015-3987
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3987: Exosomal microRNA in cell-free urine samples as a source for liquid prostate cancer biopsy

Abstract: MicroRNAs constitute a class of small cellular RNAs (typically 19-23 nt) that function as post-transcriptional regulators of gene expression. Current estimates indicate that more than one third of the human cellular transcriptome is regulated by this small class of RNA (∼2000 miRNA). MicroRNAs have been shown to be actively exported from tissues into the circulation through a variety of mechanisms including complexing with RNA binding proteins or HDL and through active exosome transport. Exosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some investigations have reported that exosomes may even determine which organ is targeted by metastasis (18). The use of patient blood and other bodily fluids to isolate exosomes (liquid biopsy) provides a real-time, non-invasive method to monitor disease progression and determine therapy options (1921). Additionally, exosomes are now being studied as therapeutic delivery agents for treating many diseases, including targeting CSCs (2225).…”
Section: Introductionmentioning
confidence: 99%
“…Some investigations have reported that exosomes may even determine which organ is targeted by metastasis (18). The use of patient blood and other bodily fluids to isolate exosomes (liquid biopsy) provides a real-time, non-invasive method to monitor disease progression and determine therapy options (1921). Additionally, exosomes are now being studied as therapeutic delivery agents for treating many diseases, including targeting CSCs (2225).…”
Section: Introductionmentioning
confidence: 99%